EAPS group history, Appearance concept, and summary of the results: ten years of research, teaching, and extension on the theme Aging and Appearance - Lopes, Andrea (2019)
The Aging and Appearance theme has not been discussed in the Brazilian Gerontology in its complexity. The article presents the activities, results, and challenges present in the 10 years of the research, teaching and extension group Aging, Appearance and Meaning of the School of Arts, Sciences, and Humanities from University of São Paulo, Brazil. The group's contributions were: 1) the proposition of a theme of scientific investigation, from the observation of a specific social demand; 2) the proposition of a concept for the appearance variable; 3) university extension workshop in conjunction with an elective discipline involving undergraduate and graduate students; 4) three artistic exhibitions; 5) various lectures; 6) a set of exploratory research, mostly qualitative, developed by undergraduate and graduate students, some with funding; 7) a research seminar; 8) registration in CNPq Research Groups Directory, Brazil; 9) institutional website and Facebook page; and, finally, 10) national scientific publications, including the organization of a special issue on the subject for the Kairós Gerontologia Journal.